Determinants of Confidence in Overall Knowledge About COVID-19 Among Healthcare Workers in South Africa: Results From an Online Survey - Manyaapelo, Thabang; Mokhele, Tholang; Sifunda, Sibusiso; Ndlovu, Philisiwe; Dukhi, Natisha; Sewpaul, Ronel; Naidoo, Inbarani; Jooste, Sean; Tlou, Boikhutso; Moshabela, Mosa; Mabaso, Musawenkosi; Zuma, Khangelani; et al. (Frontiers in Public Health, 2021)
Background: Adequate information and knowledge about COVID-19 has been shown to induce the confidence and positive performance among healthcare workers (HCWs). Therefore, assessing the relationship between confidence in knowledge and associated factors among HCWs is vital in the fight against COVID-19. This paper investigates factors associated with HCWs’ confidence in their overall knowledge about COVID-19 in South Africa in the early stages of the epidemic. Methods: Data utilized in this paper were from an online survey conducted among HCWs using a structured questionnaire on a data free online platform. The study population were all the medical fraternity in South Africa including medical and nurse practitioners as well as other health care professionals. Bivariate and multivariate logistic regression models were performed to examine the factors associated with confidence in HCWs’ overall knowledge about COVID-19. Results: Overall, just below half (47.4%) of respondents indicated that they had confidence in their overall knowledge about COVID-19. Increased odds of having confidence in the knowledge about COVID-19 were significantly associated with being male (aOR = 1.36 95% CI [1.08-1.71], p<0.05), having a doctorate degree (aOR = 1.84 [1.12-3.01], p<0.05), being satisfied with the information about COVID-19 guidelines (aOR = 8.94 [7.39-10.82], p<0.001) and having already treated COVID-19 patients (aOR = 1.74 [1.31-2.29], p<0.001). Those who were highly concerned with the levels of training of HCWs (aOR = 0.39 [0.20-0.76], p<0.05) had decreased odds of having confidence in their overall knowledge about COVID-19. Conclusion: This study sheds light on the importance of capacitating HCWs with knowledge and adequate relevant training as part of infection prevention control measures during pandemics. Future training and information sharing should be sensitive to knowledge gaps by age, gender, qualifications, professional categories and experience.